2021
DOI: 10.52403/ijshr.20210427
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Clinical and Radiographic Outcomes of Indirect Pulp Treatment with Silver Diamine Fluoride Versus Calcium Hydroxide in Primary Teeth: A Randomized Controlled Trial

Abstract: Background: Indirect pulp treatment (IPT) has been a minimally invasive procedure for deep dentinal caries with considerable success. IPT is a procedure which involves excavation of infected dentin and keeping affected dentin intact, followed by application of IPT agent and restoration. The aim of the study was to evaluate and compare clinical and radiographic outcomes of IPT with silver diamine fluoride (SDF) and calcium hydroxide in primary teeth. Materials and Methods: The present study is a prospective, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(11 reference statements)
1
3
0
Order By: Relevance
“…An indirect pulp treatment procedure not only maintains the vitality of the carious tooth, but also lowers the number of microorganisms near the pulp and halts the progression of caries. The success rate in the current study was 96.0% in the SDF Group and 91.6 % in the light-cured calcium hydroxide group at the end of 12-month follow up period, and the difference among the groups was statistically not-significant (p>0.05), which is consistent with earlier studies reported by Patil et al 21 , who found that SDF had a 98 % success rate and calcium hydroxide had an 88% success rate when used as IPT agents in primary teeth.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…An indirect pulp treatment procedure not only maintains the vitality of the carious tooth, but also lowers the number of microorganisms near the pulp and halts the progression of caries. The success rate in the current study was 96.0% in the SDF Group and 91.6 % in the light-cured calcium hydroxide group at the end of 12-month follow up period, and the difference among the groups was statistically not-significant (p>0.05), which is consistent with earlier studies reported by Patil et al 21 , who found that SDF had a 98 % success rate and calcium hydroxide had an 88% success rate when used as IPT agents in primary teeth.…”
Section: Discussionsupporting
confidence: 91%
“…There are very few studies available in the literature comparing SDF and calcium hydroxide as IPT agents in primary teeth. 21,22 The aim of this randomized clinical trial is to compare the efficacy of diluted SDF (1:10) and light-cured Ca(OH)2 as indirect pulp capping agents in primary molars with deep carious lesions.…”
mentioning
confidence: 99%
“…Comparable, if not higher, clinical and radiographic success rates have been demonstrated by SDF in preventing caries and promoting pulp repair. Furthermore, advancements like light-cured SDF and the modified Hall technique with SDF have demonstrated encouraging outcomes in terms of improving the efficacy of SDF in IPT operations [66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed a 96% success rate for the SDF group and an 88% success rate for the calcium hydroxide group in the same time frame. However, there was no statistically significant difference between the two groups [68]. Shafi et al (2022) conducted an RCT to evaluate diluted SDF against calcium hydroxide with a light cure used as an IPC material in primary molars.…”
Section: Silver Diamine Fluoride As An Indirect Pulp Therapy Material...mentioning
confidence: 99%